Investigating Food Insecurity and Its Socioeconomic Factors in Older People - Marziye Shabani; Parand Pourghane; Marjan Mahdavi-Roshan; Zahra Atrkar Roushan (Journal of Holistic Nursing and Midwifery)
Introduction: Older people are a vulnerable group whose poor nutritional status contributes to the development of diseases and increased health costs. Objective: This study investigated food insecurity and its socioeconomic factors among older people visiting comprehensive health centers in East Guilan, north of Iran. Materials and Methods: This cross-sectional analytical study was conducted on 245 older people referred to comprehensive health centers in East Guilan. The sampling method was a multi-stage clustering method. The data were collected using the socioeconomic status (SES) questionnaire, the household food insecurity access score (HFIAS), and demographic characteristics through interviews. Data analysis was performed using statistical methods, including a univariate chi-square test and a multiple logistic regression analysis, to examine the simultaneous effect of independent variables on severe food insecurity. Results: The mean age of the samples was 67.66±6.059 years, 50.6% were male, and 49.4% were female. In terms of food security, 0.4% had complete food security, 11.8% had mild insecurity, 43.7% had moderate food insecurity, and 44.1% had severe food insecurity. In terms of SES, 50.2% were too inadequate, 38% were inadequate, 11.4% were partially adequate, and 0.4% were adequate. The mean food insecurity index was 14.37±5.123. At the 95% confidence level, the relationship between food security and situation of socioeconomic (OR=1.839, 95% CI, 1.497, 2.338, P=0.001), marital status (OR=0.589, 95% CI, 0.370, 0.938, P=0.001), income (OR=2.202, 95% CI, 1.541, 2.974, P=0.001), education (OR=1.735, 95% CI, 1.127, 2.669, P=0.001), the number of family workers (OR=1.411, 95% CI, 1.054, 1.876, P=0.001) were significant. Conclusion: According to the results of the present study, the majority of people (43.7%) experienced moderate food insecurity. Notably, at higher levels of SES, the level of food insecurity was lower. Also, there was a significant positive relationship between the severity of food insecurity and low SES.